2018
DOI: 10.15408/ijee.v5i2.10923
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting Critical Incident as a Form of English Teachers’ Professional Development: an Indonesian Narrative Inquiry Research

Abstract: Amidst the rapid development of English teaching, teacher’s professional development (TPD) is crucial for English teachers. It has been discussed in the TESOL Summit 2018 in Jakarta that the teachers demanded a TPD approach which facilitates them in sharing professional experiences with other teachers. This qualitative research would like to investigate the effectiveness of reflection with critical incident theory (CIT) framework as a form of TPD which many studies have found effective to fulfil that demand an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Furthermore, according to Putri and Kuswandono (2020), some of the CIs high school English teachers encounter in the Indonesian EFL context led them to improve their professional knowledge. Coming from the same context, Wijaya and Kuswandono (2018) observed that CIs affected three teachers' professional goals of developing and becoming good teachers. Concentrating on both novice and experienced teachers' reflections on their CIs, Molani et al (2021) carried out a study with 40 Iranian EFL teachers, and the findings suggested that there is a difference among practitioners' views on CIs based on their teaching experiences.…”
Section: Teacher Reflection On Critical Incidentsmentioning
confidence: 99%
“…Furthermore, according to Putri and Kuswandono (2020), some of the CIs high school English teachers encounter in the Indonesian EFL context led them to improve their professional knowledge. Coming from the same context, Wijaya and Kuswandono (2018) observed that CIs affected three teachers' professional goals of developing and becoming good teachers. Concentrating on both novice and experienced teachers' reflections on their CIs, Molani et al (2021) carried out a study with 40 Iranian EFL teachers, and the findings suggested that there is a difference among practitioners' views on CIs based on their teaching experiences.…”
Section: Teacher Reflection On Critical Incidentsmentioning
confidence: 99%
“…A critical incident is an experience, in other words, the moment that has caused change due to the importance or critical thinking placed on the event (Tripp, 2012). Critical incidents are a useful tool in research and have been utilised in education and health research either as forward focused learning opportunities (Attrill et al, 2019;Hrovat & Luke, 2016) or reflective focused moments of learning (Bolton, 2016;Nejadghanbar, 2021;Wijaya & Kuswandono, 2019). In this article the critical incidents are defined as critical when I was reflecting on what I have learnt in the Learning Agreement, making them significant in hindsight rather than at that time.…”
Section: The Article's Contributionmentioning
confidence: 99%
“…A critical incident is an experience, in other words, the moment that has caused change due to the importance or critical thinking placed on the event (Tripp, 2012). Critical incidents are a useful tool in research and have been utilised in education and health research either as forward focused learning opportunities (Attrill et al, 2019;Hrovat & Luke, 2016) or reflective focused moments of learning (Bolton, 2016;Nejadghanbar, 2021;Wijaya & Kuswandono, 2019). In this article the critical incidents are defined as critical when I was reflecting on what I have learnt in the Learning Agreement, making them significant in hindsight rather than at that time.…”
Section: It Now Records Not Only My Actions and Emotions But Also Wha...mentioning
confidence: 99%